Implementasi Total Quality Service Pada Pelayanan Jasa Perguruan Tinggi - (Jurusan Administrasi Niaga, Politeknik Negeri Semarang), Endang Sulistiyani (Teknis, 2014)
In order to enter the era of global education services provided universities as the main product can not be separated from the service quality provided to internal and external customers. Total Quality Service is a paradigm for creating quality in service delivery by involving all elements of the organization. Implementation of the approach according to ISO 9000 and according to the Deming wheel in higher education management in Indonesia will consist of four major component, namely: labor market research, higher education process design, operational processes of higher education , and the delivery of competitive and qualified graduates into the labor market. In this case we need a permanent interaction between labor market research, higher education process design, operational processes of higher education, and is responsible competitive and produce quality graduates into the labor marke .Keywords: services , service quality , Total Quality Service, Competitive graduates